2007
DOI: 10.1152/ajprenal.00077.2007
|View full text |Cite
|
Sign up to set email alerts
|

Renal ischemia-reperfusion injury is prevented by the mineralocorticoid receptor blocker spironolactone

Abstract: Renal ischemia and reperfusion (I/R) injury is the major cause of acute renal failure and may also be involved in the development and progression of some forms of chronic kidney disease. We previously showed that a mineralocorticoid receptor (MR) blockade prevents renal vasoconstriction induced by cyclosporine that leads to acute and chronic renal failure (Feria I, Pichardo I, Juarez P, Ramirez V, Gonzalez MA, Uribe N, Garcia-Torres R, Lopez-Casillas F, Gamba G, Bobadilla NA. Kidney Int 63: 43-52, 2003; Perez-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
115
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 51 publications
14
115
3
Order By: Relevance
“…Interestingly, these effects of aldosterone were completely prevented by spironolactone (31). In support to this, we have recently shown that spironolactone completely prevented renal acute injury induced by ischemia-reperfusion by a mechanism that involved preservation of renal plasma flow, reestablishment of urinary NO 2 /NO 3 excretion that was accompanied by increased expression of eNOS and phosphorylation at its residue S1177, as well as by a reduction of lipoperoxidation and cell apoptotic death, indicating indeed that aldosterone also participates in hypoperfusion observed in this model (36).…”
Section: Role Of Aldosterone In Csa Nephrotoxicitysupporting
confidence: 67%
“…Interestingly, these effects of aldosterone were completely prevented by spironolactone (31). In support to this, we have recently shown that spironolactone completely prevented renal acute injury induced by ischemia-reperfusion by a mechanism that involved preservation of renal plasma flow, reestablishment of urinary NO 2 /NO 3 excretion that was accompanied by increased expression of eNOS and phosphorylation at its residue S1177, as well as by a reduction of lipoperoxidation and cell apoptotic death, indicating indeed that aldosterone also participates in hypoperfusion observed in this model (36).…”
Section: Role Of Aldosterone In Csa Nephrotoxicitysupporting
confidence: 67%
“…In addition, renal tubular apoptosis has also been shown to play a critical role in the development of this pathologic condition through induction of tubular cell damage (36). Thus, prevention of renal tubular apoptosis by IgGFc through inhibition of caspase-3 activation might also contribute to reduce both the renal tubular damage and the subsequent renal dysfunction in WT mice subjected to renal I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we cannot exclude the possibility that there was insufficient time for the rats to develop hyperkalemia. In this respect, it is important to note that, in the previously mentioned study, 9 spironolactone also did not cause hyperkalemia. Consequently, additional studies are needed to confirm that BR-4628 will not increase the risk of hyperkalemia.…”
mentioning
confidence: 51%
“…5 NOX4 expression is increased in tubular epithelial cells, mesangial cells, and podocytes cultured in highglucose media and kidney tissue from different rodent models of diabetes. [6][7][8][9][10] The deleterious effects of NOX4 in these contexts are numerous and extend beyond free radical/oxidant-mediated tissue injury. For example, in addition to reducing ROS levels, transient Nox4 knockdown has been shown to reduce Akt/PKB and extracellular signal-regulated kinase-1/2 phosphorylation in cortical homogenates from diabetic mice 8 and inhibit TGFb1-induced renal myofibroblast activation.…”
mentioning
confidence: 99%